2006
DOI: 10.1002/jmv.20656
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Hepatitis A preceding Guillain–Barré Syndrome

Abstract: A case of acute hepatitis A with Guillain-Barré Syndrome subtype AMAN (acute motor axonal neuropathy) in a 17-year-old male is reported. Serum and cerebrospinal fluid were positive for anti-hepatitis A virus (HAV) IgM, IgG, and IgA. The onset of the syndrome was evident in week 3 of illness. The remarkably high titers of serum anti-HAV IgG appeared unique to a hepatitis A patient with the syndrome. Phylogenetic analysis of the HAV genome detected in the serum and feces revealed genotype IIIA, circulating commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
(18 reference statements)
1
18
0
Order By: Relevance
“…It has also been suggested that the detection of plasma HAV RNA after 20 days of illness may predict a prolonged course of the disease [Sagnelli et al, 2003]. The GBS patient of the present study showed persistence of the HAV RNA as monitored up to 126 days by PCR and remarkably high anti-HAV titers [Chitambar et al, 2006]. The longer duration of the HAV RNA in the GBS patient may also thus be indicative of neutralization escape of the virus or a low level of antibodies that could neutralize the virus.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…It has also been suggested that the detection of plasma HAV RNA after 20 days of illness may predict a prolonged course of the disease [Sagnelli et al, 2003]. The GBS patient of the present study showed persistence of the HAV RNA as monitored up to 126 days by PCR and remarkably high anti-HAV titers [Chitambar et al, 2006]. The longer duration of the HAV RNA in the GBS patient may also thus be indicative of neutralization escape of the virus or a low level of antibodies that could neutralize the virus.…”
Section: Discussionsupporting
confidence: 57%
“…Fecal specimens were collected during 1992-2004 from patients with acute hepatitis A to study the molecular epidemiology of HAV strains from Pune, western India [Chitambar et al, 2006[Chitambar et al, , 2007. Three specimens collected during these studies were investigated for the conserved and variable features of HAV genomes.…”
Section: Specimensmentioning
confidence: 99%
See 2 more Smart Citations
“…Infections with Campylobacter jejuni, Mycoplasma pneumoniae, Cytomegalovirus and Epstein-Barr virus are each associated with GBS. In addition, it has been reported that hepatitis viruses, including hepatitis A, B and C, are possibly associated with the development of GBS (2)(3)(4). Furthermore, recent reports have suggested that hepatitis E virus (HEV) infection is linked to GBS onset (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%